2018
DOI: 10.1111/jcpe.12939
|View full text |Cite
|
Sign up to set email alerts
|

Plaque‐induced gingivitis: Case definition and diagnostic considerations

Abstract: Based on available methods to assess gingival inflammation, GC could be simply, objectively and accurately identified and graded using bleeding on probing score (BOP%) CONCLUSIONS: A patient with intact periodontium would be diagnosed as a GC according to a BOP score ≥ 10%, further classified as localized (BOP score ≥ 10% and ≤30%) or generalized (BOP score > 30%). The proposed classification may also apply to patients with a reduced periodontium, where a GC would characterize a patient with attachment loss an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
212
1
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(263 citation statements)
references
References 207 publications
(408 reference statements)
2
212
1
12
Order By: Relevance
“…We used a gingival inflammation threshold of 10% FMBS, as reported by the current case definition of gingivitis, and a threshold >30% for generalized gingival inflammation [39]. Previous investigations demonstrated that self-reported bleeding was a symptom with high specificity, but low sensitivity [13,14,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a gingival inflammation threshold of 10% FMBS, as reported by the current case definition of gingivitis, and a threshold >30% for generalized gingival inflammation [39]. Previous investigations demonstrated that self-reported bleeding was a symptom with high specificity, but low sensitivity [13,14,46].…”
Section: Discussionmentioning
confidence: 99%
“…The self-awareness of gingival bleeding was calculated by comparing self-reported gingival bleeding with FMBS values. Based on the current literature, the cut-off point for gingival inflammation was set at 10% of FMBS [39]. Thus, subjects with FMBS < 10% who did not self-perceive gum bleeding, as well as subjects with FMBS ≥ 10% who self-perceived gum bleeding were considered aware of their gingival health status.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Periodontal status was defined following the latest available EFP/AAP consensus for gingivitis and periodontitis cases [40,41] and used as categorical independent variables. A gingivitis case was defined if a total score of BoP ≥ 10% [41]. Periodontitis case was defined if interdental CAL is detectable at ≥2 non-adjacent teeth, or buccal or oral CAL ≥ 3 mm with PPD > 3 mm at ≥2 teeth.…”
Section: Periodontal Examinationmentioning
confidence: 99%
“…Essa publicação é um esforço conjunto da Academia Americana de Periodontia e da Federação Europeia de Periodontia e substitui a classificação até então vigente 2 . Nessa edição de 291 páginas, há 18 artigos relacionados [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , além do relato de consenso de cada um dos quatro grupos de trabalho [21][22][23][24] e uma introdução 1 . A introdução à nova classificação apresenta-se resumida e faz frequentes menções (inclusive com a disponibilização de link) a artigos originais, tornando uma primeira familiarização com a nova classificação dependente de leituras mais aprofundadas.…”
Section: No Mês De Junho De 2018 Foi Lançado O Proceedings Do Workhunclassified